Caracterização das escórias provenientes da reciclagem de baterias de chumbo-ácido - Andrade, Micheli Barbosa de (2011)
In Brazil, the main source of lead metal is derived from recycled lead-acid batteries by the pyrometallurgical process. The process consists in separating the components of lead-acid battery and subsequent fusion of the metal in the furnace to reduce the rotational type. Recycling is an economical alternative, sustainable and environmentally friendly but, recycling industries are potentially polluting. During the process, there is generating a large amount of slag, which may contain metals that were present in raw material or that were added to the reactions necessary to promote the recycling process. This slag is classified as Class I waste, hazardous waste, according to Brazilian standard NBR 10004 Brazilian Association of Technical Standards and (ABNT) and must have as the final destination of hazardous waste landfill. The contribution of this paper lies in the chemical evaluation of the slag from the recycling of lead batteries; structural characterizations, indicate that in turn, forms of association of the metal, and their potential to mobilize heavy metals from the method of Tessier (Method of selective extraction applied to soils and sediments) applied to the residue in order to evaluate the conditions in which metals can be removed in the same. Data from x-ray fluorescence (XRF) showed a predominance of the elements Fe, Si, S, Al, Ca, Pb and Zn, with the initial sample had a higher quality metals and in a much higher sample. By x-ray diffraction was obtained to confirm these associated elements, forming compounds. The fayalite was present in all samples, mainly in lower and central samples, as well as lead sulfide and iron sulfide, the large overlap of the peaks difficult to visualize the phases. The evaluation of the mobilization of metals from the Tessier method and comparison with the VMP CONAMA 357 demonstrated the potential risks, direct or indirect, of the mobilization of these metals. With the application of different conditions of leaching of the method of Tessier, one can observe that treatment of these slags in pH 5.0 extracts about 90% of lead present in the slag.